Potential of adiponectin as a cardioprotective agent. (November 2007) - Shibata, Rei; Ouchi, Noriyuki; Walsh, Kenneth; Murohara, Toyoaki
In this review, we focus on the role of adiponectin as a cardioprotective agent in several pathological heart conditions. Obesity is closely associated with Type 2 diabetes, hypertension and heart disease. Adiponectin is an adipose tissue-derived hormone whose concentration is downregulated in subjects with obesity-related diseases. Hypoadiponectinemia has been identified as an independent risk factor for Type 2 diabetes, coronary artery disease, acute coronary syndrome and hypertension. More recent experimental findings have shown that adiponectin directly affects signaling in cardiac myocytes and has beneficial effects on several pathological heart conditions, including cardiac hypertrophy and myocardial infarction. The favorable effects of adiponectin are associated with attenuated inflammatory response, decreased myocyte death, decreased hypertrophic response, maintained ischemia-induced angiogenesis and reduced interstitial fibrosis. Therefore, adiponectin could represent a molecular target for treating obesity-linked cardiac diseases.